Applying agile principles in enterprise architecture - Ndoro, Hakunavanhu Gilbert (Department of Information Systems, 2025)
Background: Modern enterprises, regardless of the type of industry, are operating in a dynamic global landscape characterised by rapid technological advancements, shifting regulations and customer preferences. In this complex environment, staying in business presents significant challenges for modern enterprises. Agile enterprise architecture (AEA) is considered a solution to these challenges. However, there is limited empirical evidence and theory to guide the application of agile principles (AP) in enterprise architecture (EA). Objectives: The objectives of this study are to explain: 1. How can an enterprise apply AP in EA to reduce EA ambiguity? 2. How can an enterprise apply AP in EA to reduce enterprise complexity? 3. How can AP make an EA project adapt to the enterprise's needs and changes? 4. What are the barriers of applying AP in EA? Design/methodology/approach: The study employed a cross-sectional explanatory qualitative multi-case study, utilising primary and secondary data. Two global financial services technology companies participated in the study. Primary data was collected by interviewing six research participants to address the research questions. Secondary data was obtained in the form of eleven documents. Thematic analysis was applied using a computer-aided qualitative data analysis software called NVivo. Findings: The study explained the agile delivery process, emphasising essential concepts associated with its execution. A well-executed agile delivery process was found to decrease EA ambiguity, which, in turn, reduces overall enterprise complexity. With the proper processes to address challenges such as culture, skills, resistance to change, centralised control, as well as agile processes taking precedence over business value and EA serving as a bottleneck, AP were identified as a means to assist EA projects in adapting to changing enterprise needs.